2019
DOI: 10.1111/str.12316
|View full text |Cite
|
Sign up to set email alerts
|

Fracturing behaviour of sandstone specimens with a cavity formed by intersecting excavations under compression: Experimental study and numerical modelling

Abstract: To investigate the mechanical properties, damage characteristics, and fracturing behaviour of specimens with a cavity formed by intersecting excavations, a series of uniaxial compression tests were conducted incorporating digital image correlation (DIC) and acoustic emission (AE) techniques. PFC 2D modelling was conducted to further study the failure modes and crack evolution under biaxial loading. The results showed that the mechanical properties are significantly weakened by the cavity and influenced by its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…The excavation damaged zone (EDZ) is affected by multiple factors, such as unloading rate, rock lithology, tunnel shape, and in situ stresses . It is widely confirmed that tunnel shape plays an important role in affecting the failure intensity and destruction area of tunnels at great depth . This is primarily because the stress concentration, displacement, and deformation distribution are strongly related to the tunnel structure (straight line or curve) and cross‐sectional area.…”
Section: Introductionmentioning
confidence: 99%
“…The excavation damaged zone (EDZ) is affected by multiple factors, such as unloading rate, rock lithology, tunnel shape, and in situ stresses . It is widely confirmed that tunnel shape plays an important role in affecting the failure intensity and destruction area of tunnels at great depth . This is primarily because the stress concentration, displacement, and deformation distribution are strongly related to the tunnel structure (straight line or curve) and cross‐sectional area.…”
Section: Introductionmentioning
confidence: 99%
“…e excavation depth for metal mines worldwide has reached −1000 m to −2000 m, and the maximum mining depth is over −4000 m [1]. e in-situ stress for deep mines is normally high, which results in more and more mining/ excavation-induced hazards, including rockburst, roof collapses, and shaft failure.…”
Section: Introductionmentioning
confidence: 99%
“…Basic modes of crack extension are sketched in Figure 1. In the rock mechanics and the fracture mechanics literature, a large number of studies have been devoted to the study of initiation, propagation and coalescence of cracks in rocks and brittle materials under different loading conditions (Gehle and Kutter 2003;Kulatilake et al 2001;Le et al 2018;Lee and Jeon 2011;Lee and Ravichandran 2003;Manouchehrian et al 2014;Park and Bobet 2010;Wang et al 2011;Wong and Einstein 2009;Wong and Chau 1998;Wu et al 2019c;Yang et al 2013;Zhang et al 2009;Zhuang et al 2014). These studies revealed many fracturing characteristics of rocks and led to the improvement of safety in rock structures.…”
Section: Introductionmentioning
confidence: 99%